Aplicação de um sistema de controle baseado no comportamento do usuário em um refrigerador comercial de bebidas - Pabon, Yeyner Alveiro Carrillo (2023)
Refrigeration systems are of great importance in industrial, commercial, and residential areas, being essential for food preservation, beverage cooling, thermal comfort, and medicines, among others. It is notable that these systems have a high consumption of electricity to maintain a controlled temperature and thus guarantee the quality of the products. Currently, most refrigeration systems do not have controls based on user behavior. Thus, the optimization of the control systems is fundamental for the refrigeration systems to have a reduction in the consumption of electric energy. In this way, this work aims to develop an ON/OFF control strategy that reduces the consumption of electricity in a beverage refrigeration system based on the user's consumption behavior. To carry out this work, data were collected from a beverage cooler over three months. Based on these data, an ON/OFF control strategy with variable reference was developed, which modified the control Setpoint, based on the prediction made by the multiplicative model, which identified the user's consumption pattern. When comparing the control systems, there was a reduction in the cycling frequency and in the refrigerator's electricity consumption by up to 100% and 41.4%, respectively, during the period when there was no beverage consumption. In addition, a reduction in cycling and monthly electricity consumption of 50% and 18.4%, respectively, was obtained when using the proposed control system continuously. This reduction in electricity consumption has a direct impact on the operating costs of the system, in addition to reducing indirect impacts and reducing current peaks, increasing the useful life of the equipment. Under these conditions, it is concluded that, in comparison with the conventional ON/OFF system, the methodology proposed in this work showed better performance in relation to the consumption of electrical energy, in addition to the results suggesting an increase in the useful life of beverage refrigeration systems.